A76 Inequalities in the distribution of primary care providers: Comparing healthcare disparity among urban and rural Floridian. Issue 2 (June 2015) - Steiner, Ruth; Bejleri, Ilir; Neff, Donna; Harman, Jeff; Lutz, Barbara; Yoon, Sulhee; Bumbach, Michael
Abstract: Background: Many economics, sociology, and urban planning researchers have assessed regional inequalities, especially for those populations affected by socioeconomic factors such as low income and unemployment status. Inequalities regarding health and its providers have been documented in the last few decades. In 2010, the Department of Human and Health Service (DHHS) launched the Healthy People 2020 movement with goals to eliminate health inequality/disparity and to encourage healthy development. According to the DHHS, health disparity is defined as "a particular type of health difference that is closely linked with physical distance to service, social, economic, and/or environmental disadvantage". Health disparity that results from the limited access to healthcare facilities is believed to be associated with the unequal distribution of resources and opportunities such as healthcare service, physical activity facilities, and healthy food. However, empirical studies are insufficient for understanding the extent and magnitude of health disparities in the United States. This study seeks to use the inequality of distribution of healthcare providers as a measure for spatial health disparities in urban and rural areas (AIM1) while also monitoring socioeconomic characteristics of the populations in said areas (AIM2). Methods: For the first aim, this study will calculate the population per physician ratio for each urban and rural census tract boundary in Florida. The Gini coefficient and Lorenz curve are used to measure the sufficiency or the insufficiency of physician distribution for each urban and rural Florida. These measures are designed to analyze inequality of income or wealth, but they also have been used to study the distribution of health resources such as physician distribution. Second, this study will use Hot Spot Analysis in Geographic Information System (GIS) to calculate the Getis-Ord GI statistic to identify patterns of disadvantaged socioeconomic populations. Cluster areas with high or low densities of certain socioeconomic characteristics, hot spots, will be determined. Results: Preliminary results present that primary care physicians in both urban and rural areas of Florida were unevenly distributed. The Gini coefficient for the distribution of primary care physicians in urban Florida was 0.49 (SD=0.0001), while that of the rural Florida was 0.38 (SD=0.01). Conclusions: The inequality in the distribution of primary care physicians was higher in urban areas compared with that of the rural Florida. For this purpose, the availability (number) of physicians could be adjusted depending on socioeconomic factors.